1988
DOI: 10.1128/jcm.26.4.654-661.1988
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of specific immunoglobulins M, E, A, and G in congenital, primary, and secondary cytomegalovirus infection studied by antibody-capture enzyme-linked immunosorbent assay

Abstract: Antibody-capture enzyme-linked immunosorbent assay (ELISA) using enzyme-labeled cytomegalovirus (CMV) nuclear antigen is a reliable and easily performed test suitable for routine use. As the serologic response to CMV infection may, however, vary considerably among patients, we have studied the kinetics of CMV-specific immunoglobulin M (IgM), IgE, IgA, and IgG antibodies in 352 sera from 61 patients by using antibody-capture ELISA and complement fixation (CF) tests. In a CMV mononucleosis group (n = 17), most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
0
3

Year Published

1992
1992
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 28 publications
3
32
0
3
Order By: Relevance
“…For this reason we decided to assign a positive result exclusively to a serum sample with reactivity to at least one band in the recombinant section of the blot and at least one band in the viral section of the blot. By using this algorithm, 1% of sera from blood donors appear to have HCMVspecific IgM, as detected by the newWB, which is consistent with the normal rate of infection in healthy adults (18,19). Furthermore, 100% of the IgM-positive sera were shown to be positive by newWB, indicating a very high sensitivity of the novel test.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…For this reason we decided to assign a positive result exclusively to a serum sample with reactivity to at least one band in the recombinant section of the blot and at least one band in the viral section of the blot. By using this algorithm, 1% of sera from blood donors appear to have HCMVspecific IgM, as detected by the newWB, which is consistent with the normal rate of infection in healthy adults (18,19). Furthermore, 100% of the IgM-positive sera were shown to be positive by newWB, indicating a very high sensitivity of the novel test.…”
Section: Discussionsupporting
confidence: 64%
“…Human cytomegalovirus (HCMV)-specific immunoglobulin M (IgM) is a sensitive and specific indicator of primary HCMV infection in immunocompetent subjects and is often produced during active viral reactivation in immunocompromised patients (1,4,17,19,24). Serum IgM to HCMV can be detected by a variety of different procedures, but its detection has been hampered by several technical problems causing interassay variability.…”
mentioning
confidence: 99%
“…These reports emphasize the general importance of IgA serodiagnosis for the identification of acute primary and secondary HCMV infection. One of the preceding studies has reported a poor sensitivity of IgA-specific serodiagnosis in neonates with congenital or acquired HCMV infection (7). These findings are confirmed Immunocompetent individuals with HCMV infections c (10) 9 9 9 2 6 2 5 5 6 6…”
supporting
confidence: 52%
“…Several preceding studies have investigated the IgA-specific immune response against cell culture-derived antigens in different stages of HCMV infection (1,3,(7)(8)(9). These reports emphasize the general importance of IgA serodiagnosis for the identification of acute primary and secondary HCMV infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation